Physical Disabilities Therapeutic Implications - Tan, Uner (IntechOpen, 2017)
This book, Physical Disabilities - Therapeutic Implications, presents reports on a wide range of areas in the field of neurobiological disabilities, including movement disorders (Uner Tan syndrome, genetic and environmental influences, chronic brain damage, stroke, and pediatric disabilities) related to physical and stem cell therapy. Studies are presented from researchers around the world, looking at aspects as wide-ranging as the genetics, wheelchair, and robotics behind the conditions to new and innovative therapeutic approaches.